2018
DOI: 10.1007/s10800-018-1154-x
|View full text |Cite
|
Sign up to set email alerts
|

An aluminium battery operating with an aqueous electrolyte

Abstract: Aluminium is an attractive active material for battery systems due to its abundance, low cost, a gravimetric energy density of 2.98 Ah g −1 (c.f. lithium 3.86 Ah g −1 ) and a volumetric energy density of 8.04 Ah cm −3 (c.f. lithium 2.06 Ah cm −3 ). An aqueous electrolyte-based aluminium-ion cell is described using TiO 2 nanopowder as the negative electrode, CuHCF (copper-hexacyanoferrate) as the positive electrode and an electrolyte consisting of 1 mol dm −3 AlCl 3 and 1 mol dm −3 KCl. Voltammetric and galvano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 20 publications
0
59
0
Order By: Relevance
“…Holland et al. initially found poor specific capacities for TiO 2 particles (actual 10 mAh g −1 vs. theoretical 335 mAh g −1 ), leading them to propose that the reaction TiO 2 + x Al 3+ +3 x e − ⇄Al x TiO 2 occurs only on surface sites . Lahan and Das later demonstrated this low specific capacity to be an artefact of poor electronic percolation within the active material, that is, they were able to achieve an enhanced capacity (52 mAh g −1 ) by compositing TiO 2 nanoparticles with conductivity‐enhancing graphite, and confirmed lattice changes to match with Al 2 TiO 5 and Al 2 Ti 7 O 15 phases through XRD and TEM analyses …”
Section: Trends In Enabling Aqueous Electrolytes For Multivalent‐ion mentioning
confidence: 99%
See 2 more Smart Citations
“…Holland et al. initially found poor specific capacities for TiO 2 particles (actual 10 mAh g −1 vs. theoretical 335 mAh g −1 ), leading them to propose that the reaction TiO 2 + x Al 3+ +3 x e − ⇄Al x TiO 2 occurs only on surface sites . Lahan and Das later demonstrated this low specific capacity to be an artefact of poor electronic percolation within the active material, that is, they were able to achieve an enhanced capacity (52 mAh g −1 ) by compositing TiO 2 nanoparticles with conductivity‐enhancing graphite, and confirmed lattice changes to match with Al 2 TiO 5 and Al 2 Ti 7 O 15 phases through XRD and TEM analyses …”
Section: Trends In Enabling Aqueous Electrolytes For Multivalent‐ion mentioning
confidence: 99%
“…On a per ion basis, this would be a charge vector superior to that of elemental lithium . Indeed, transposing concepts from the aqueous lithium system to other water‐based chemistries, recent reports have demonstrated remarkable breakthroughs with heavier elements, for example, Na, Mg, Al, K, Ca, Cu, Fe, Zn, Mn, Rb/Tl, and V . We aim to contribute insights to push these further, by focusing on low‐cost, multivalent‐ion (Mg, Ca, Zn, Al) battery development from an electrolyte point of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gao and co‐workers reported that a type of copper‐hexacyanoferrate (CuHCF) has been synthesized, delivering a capacity of 41 mAh g −1 at 400 mA g −1 in 0.5 m Al 2 (SO 4 ) 3 aqueous electrolyte with acceptable capacity retention of 55 % after 1000 cycles . Wills and co‐workers also illustrated the availability of CuHCF as cathode material for aluminum‐ion batteries with an energy density of 15 mW h g −1 at a power density of 300 mW g −1 . Menke and co‐workers described CuHCF as a cathode material for aluminum‐ion batteries in an organic electrolyte, which delivered a reversible capacity of approximately 10 mA h g −1 at 50 μA cm −2 …”
Section: Introductionmentioning
confidence: 99%
“…This has opened up new challenges as well as opportunities in the realization of more efficient aqueous ZIBs (AZIBs) with a variety of other cathode materials . Although other chemistries based on Al/Al 3+ and Mg/Mg 2+ have been proposed, the Zn/Zn 2+ systems are considered to be the leading candidate due to the high theoretical capacity (820 mAh g −1 ), low redox potential (−0.76 V vs standard hydrogen electrode [SHE]), natural abundance, and low cost of Zn metal …”
Section: Introductionmentioning
confidence: 99%